Genome-wide screening for understanding the role of DNA methylation in colorectal cancer. (October 2013) - Sipos, Ferenc; Mũzes, Györgyi; Patai, Árpád V; Fũri, István; Péterfia, Bálint; Hollósi, Péter; Molnár, Béla; Tulassay, Zsolt
DNA methylation analysis methods have undergone an impressive revolution over the past 15 years. Regarding colorectal cancer (CRC), the localization and distribution of several differently methylated genes have been determined by genome-wide DNA methylation assays. These genes do not just influence the pathogenesis of CRC, but can be used further as diagnostic or prognostic markers. Moreover, the identified four DNA methylation-based subgroups of CRC have important clinical and therapeutic merit. Since genome-wide DNA methylation analyzes result in a large amount of data, there is a need for complex bioinformatic and pathway analysis. Future challenges in epigenetic alterations of CRC include the demand for comprehensive identification and experimental validation of gene abnormalities. By introduction of genome-wide DNA methylation profiling into clinical practice not only the patients' risk stratification but development of targeted therapies will also be possible.